Life cycles of vermicomposting earthworms. - Domínguez, Jorge; Gómez-Brandón, María (Instituto de Ecología, A.C., 2010)
After three decades of investigation in the field of vermicomposting the scope of this biotreatment of organic residues has been greatly amplified. New findings into life cycles and optimal growth conditions of species already used, added to the introduction of new species from different ecological categories capable of processing different types of residues have made this possible. The majority of these new species come from tropical regions, where the development of vermicomposting is promising, given the current problems in the treatment and management of these residues, and limited funding. Moreover, the use of local endemic species appears to be a good alternative as they are well adapted to local environmental conditions. The aim of this review is to compile and update the knowledge related to life cycles and environmental limitations of the earthworm species suitable for the vermicomposting process.